“A Study to Assess the Knowledge Regarding Stem Cell Therapy and Its Benefits among B.Sc. Nursing 3rd Year Students” - Mr. Shreyash khade,; Mr. Sarvesh Harne,; Mr. Satyam Lavand,; Ms. Rebecca More,; Ms. Rechal Mascarenhas,; Ms. Prerana Ranbhise,; Ms. Rajarshi Minachekar,; Mrs. Sunanda Kale, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
BACKGROUND: Stem cells are undifferentiated cells with the remarkable ability to regenerate and develop into various cell types, offering potential for treating over 75 life threatening diseases. Stem cell therapy, particularly through umbilical cord blood, is a promising approach for conditions like diabetes, heart disease, and spinal cord injuries. In India, stem cell transplantation has been slower to progress, with around 500 procedures performed to date, but its potential, especially in treating conditions like thalassemia and chronic myeloid leukemia, is growing. Objective: To assess the knowledge of B.Sc. Nursing 3rd year students regarding stem cell therapy and its benefits. To find out an association between level of knowledge score with selected sociodemographic variables among B.Sc. Nursing 3rd year students. Methods: - The research approach adopted for the study was quantitative, descriptive survey design was used for this study. By Non probability convenience sampling technique 83 B.Sc. Nursing students were selected from D.Y. Patil College of Nursing at Kolhapur. 33 Structured knowledge questionnaires were used to assess the knowledge regarding stem cell therapy and its benefits. Result: -The study finding of the knowledge related stem cell therapy and its benefits among B.Sc. Nursing 3rd years students was (49%) Good, (35%) Average, and (16%) Poor knowledge. Chi-square values indicate a significant association between the knowledge scores of B.Sc. Nursing 3rd years students with gender (5.991 at 0.05 levels)and Source of information (9.488 at 0.05 levels), But there is no significant association between the knowledge scores of among B.Sc. Nursing 3rd years students and other demographic variables such as Age in years, Religion. Interpretation and Conclusion: -The study concludes that the level of knowledge regarding stem cell therapy and its benefits among B.Sc. Nursing 3rd-year students at D. Y. Patil College of Nursing, Kolhapur, is moderate, with 49% of participants demonstrating good knowledge. There is a need to enhance the understanding of stem cell therapy by incorporating updated curriculum and conducting workshops to provide students with a deeper insight into this field.